Understanding Investment Decisions Through the Lens of Behavioral Biases: A Moderated Mediation Approach (Journal of Asian Development Studies, 2025)
With an emphasis on the moderating influence of financial literacy and the mediating role of risk tolerance, this study examines the relationship between behavioral biases – specifically, impulsivity and herding – and investment decisions. Purposive and snowball sampling were used to select 300 financially independent investors in Lahore, Pakistan, between the ages of 20 and 45, and structured questionnaires were used to gather quantitative data. The moderated mediation effects were examined using Process Hayes Model 58. The results reflect that with high-risk tolerance, impulsivity and herding both have a significant impact on investing behaviors. On the other hand, financial literacy acts as a potent moderator, lowering impulsive decision-making and unreasonable risk-taking. These findings demonstrate how critical financial literacy is as a behavioral and cognitive guard when making financial decisions. Policymakers, educators, and financial advisors who want to create intervention strategies that promote sensible investing practices can benefit from the study’s practical implications. It closes a significant gap in the behavioral finance literature by being one of the first to empirically show a double moderated mediation pathway involving these behavioral constructs in a developing country setting.